2018
DOI: 10.1158/1078-0432.ccr-17-3871
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Cancer Patient-Derived Xenografts Enable Characterization of Cancer Stem Cells and New Gene Events Associated with Tumor Progression

Abstract: Salivary gland cancers (SGC) frequently present with distant metastases many years after diagnosis, suggesting a cancer stem cell (CSC) subpopulation that initiates late recurrences; however, current models are limited both in their availability and suitability to characterize these rare cells. Patient-derived xenografts (PDX) were generated by engrafting patient tissue onto nude mice from one acinic cell carcinoma (AciCC), four adenoid cystic carcinoma (ACC), and three mucoepidermoid carcinoma (MEC) cases, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…Salivary gland malignancies often show distant metastases several years after initial diagnosis, suggesting a subpopulation of cancer stem cells (CSCs) responsible for the late recurrences; however, the available models to characterize these rare cells are still limited. 29 In general, in salivary gland tumors; the hypothesis of cancer stem cell has not been fully examined. 30 Studies on other types of cancer revealed that cancer stem cells play a functional role in therapy resistance and tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary gland malignancies often show distant metastases several years after initial diagnosis, suggesting a subpopulation of cancer stem cells (CSCs) responsible for the late recurrences; however, the available models to characterize these rare cells are still limited. 29 In general, in salivary gland tumors; the hypothesis of cancer stem cell has not been fully examined. 30 Studies on other types of cancer revealed that cancer stem cells play a functional role in therapy resistance and tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Gene fusions remarkably alter gene structures leading to mutated protein products with an aberrant molecular function. They are usually involved in tumor progression through modulation of tumorigenic potential of the cancer stem cells [23]. The present study identified the high expression of BMX-ARHGAP fusion in GC.…”
Section: Discussionmentioning
confidence: 54%
“…For those ‘personalized medicine’-intended purposes, the creation of ex vivo 3D tumor spheroids in multi-well plates [37] can serve as a reliable method for rapid drug screening assays. Multiple salivary gland cancers, including ACCs, have sphere-forming potential and share common ex vivo phenotypes in that similar (ALDH + CD44 high ) epithelial tumor stem cell populations form the highest numbers of spheres [38]. While this system is superior in the rapid evaluation of tumor stem cells and/or their response to drug or radiation-related therapeutics, the spheres created through cell sorting currently do not include the surrounding cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, we still obtained all ACC epithelial (cribriform, solid and tubular form) and environmental characteristics with single cell transplantations, arguably better than with undissociated subcutaneous PDX tissue as it mimicked the original human ACC biopsy. As such, PDOX can be applied to newly generated ACC primary cell lines, such as from our PDX-derived ACC11 [14], or FACS-sorted ACC epithelial tumor stem cells that are currently evaluated for PDX formation capacity [38], to compare their fidelity in maintaining similar phenotypic characteristics of the original specimen. In the future, it will be essential to determine whether ACC cell lines, which are often enriched in a specific cell type, are able to generate mixed PDOX tumors.…”
Section: Discussionmentioning
confidence: 99%